A possible role of nesfatin-1 and irisin in beneficial effect of Capparis Ovata extract on liver and kidney oxidative/ nitrosative status (Annals of Medical Research, 2021)
Aim: In order to reveal the scientific evidence for its antioxidant and metabolic activities known in folk medicine, the present study was aimed to investigate the effect of bud and fruit parts of Capparis ovata plant on some antioxidant parameters and nesfatin-1 and irisin hormones in mus musculus mice for the first time.Materials and Methods: The dry extract was obtained from bud and fruit parts of C.ovata. Twenty mus musculus mice were divided into two groups as control and C.ovata treatment group. C.ovata group was fed with 500 mg/kg C.ovata plant extract via gavage for 21 days. The nesfatin-1 and irisin levels in tissue were determined using enzyme-linked Immunosorbent assay methods. The total oxidant capacity (TOC), total antioxidant capacity (TAC), nitric oxide (NO), reduced glutathione (GSH) and gamma glutamyl transpeptidase activity levels were measured spectrophotometrically.Results: Results showed that both irisin and nesfatin-1 levels were higher in liver and kidney of C.ovata group compared to the control groups. The liver TOC level was lower and the reduced GSH level was higher in group given C.ovata. The kidney NO levels were higher in C.ovata group. The extract increased synthesis of energy regulatory hormones and also exhibited antioxidant characteristics by reducing free radicals in the liver and affecting glutathione synthesis.Conclusion: As a result, C.ovata can be used as a valuable phytotherapeutic agent in processes associated with the energy regulation and oxidative stress related many disease conditions.
Keywords: Antioxidant; caper; energy regulatory hormones; glutathione; nitric oxide